Pengembangan Kesadaran Global melalui Lokakarya Program Sekolah Penggerak dengan Tema Toleransi dan Keberagaman - Halimah, Lili (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
Indonesia is known for its diversity, both in culture, religion, language, and ethnicity. This diversity needs to be managed to create a harmonious, peaceful, and just society. The development of global awareness from an early age plays a crucial role in achieving this goal. One of the key values taught to children is tolerance. This study aims to improve principals' and educators' understanding of the values of tolerance and diversity through a structured workshop model. This study used a qualitative approach with an intervention in the form of a workshop involving principals, teachers, and education personnel. Workshop activities included presentations, group discussions, case studies, simulations, and the development of a Real Action Plan (RAN) to be implemented in their respective schools. The results showed that the workshop significantly improved participants' competency in managing multicultural learning environments and promoting inclusive values in their schools. Furthermore, this study recommends the importance of policy support from local governments to ensure the continued implementation of values of tolerance and diversity in schools. This study was limited to a relatively small number of participants in Sukabumi Regency, so the generalizability of the findings may be limited. Further research is recommended to involve more participants and use a longitudinal design to assess the long-term impact of the intervention.